Алгоритм адаптивного управления импульсным высоковольтным источником питания системы электрофильтрации экологически опасных промышленных выбросов - Богуславский, Л. З.; Мирошниченко, Л. Н.; Овчинникова, Л. Е.; Козырев, С. С. (НТУ "ХПИ", 2015)
Разработан алгоритм адаптивного управления импульсным источником питания системы элек- трофильтрации, обеспечивающий корректировку параметров импульсов в соответствии с теку- щим составом экологически опасных промышленных газовых выбросов. Определены информационные координаты и каналы управляющих воздействий. Данный алгоритм дает возможность генерировать высоковольтные импульсы с параметрами, позволяющими вести эффективную деструкцию всех весомых составляющих в процессе обработки.

The research of gas emissions with different impedance as an object of processing and highvoltage impulse generator as an object of control was done. As a result the informational coordinates and control action channels were defined. Based on the experimental research with simulated model of high-voltage equipment of electrofiltration system the set of control laws and knowledgebase for adaptive control system were developed. The adaptive control algorithm for impulse generator of electrofiltration system was developed. The algorithm provides adjustments of pulse parameters according to current gas burst composition. This allows generating high-voltage impulses which provide an efficient decomposition of major components of gas emissions. Defined information coordinates and channels of control actions. Base of knowledge based on the results of experimental studies on the prototypes were made of high voltage equipment complex systems electrofiltration.
Adaptive control algorithm for high-voltage impulse generator of electrofiltration system of gas emissions with different impedance
Keywords: электрофильтрация; импульсные источники питания; управляющие воздействия; параметры импульсов генераторов; adaptive control; algorithm; switched power supplies; electrofiltration